HUBUNGAN KEKUATAN OTOT CORE STABILITY DENGAN KESEIMBANGAN DINAMIS DAN KESEIMBANGAN STATIS PADA PEMAIN SEPAKBOLA SSB IMAM BONJOL - Adi, Adi Ahmad Supendi; Donal Syafrianto; Liza; Ahmad Chaeroni (Jurnal IKEOR, 2024)
The problem in this study is that the description of core muscle strength, stability, dynamic balance and static balance in SSB Imam Bonjol football players in Padang City is not yet known This study aims to see whether there is a relationship between core muscle strength stability and dynamic balance and static balance in SSB Imam Bonjol Padang City football players. This study uses a type of Quantitative Correlation research using a one shoot model approach, which was conducted on SSB Imam Bonjol Kota Padang football players with a population of 310 players. Sampling in this study was carried out using the Purposive Sampling technique, so that the sample used as the subject in the study amounted to 20 male players with the age of 15 years, which were in accordance with and met the sample criteria. Data collection in this study was carried out using measuring instruments, to measure core muscle strength stability using the McGill Test (Flexor Endurance Test, Left Side Plank, Right Side Plank, Extensor Endurance Test), dynamic balance using Star Excursion Balance Test (SEBT) and static balance using standing stork test (SST). The data analysis technique uses a simple requirement test and correlation test, namely with a Pearson product moment. The results of the study obtained were that there was a significant correlation or relationship between core muscle strength and stability with dynamic balance and static balance in SSB Imam Bonjol Kota Padang football players with the results obtained by P Asymp. Sig. (2-tailed) < Sig. 0.05 n= 20.